(untitled) (Muitas Vozes, 2021)
The criticism regarding Clarice Lispector privileged a tendency that was concerned with the analysis of the self and the flow of consciousness, linked both to a psychological and existentialist reading of her work, highlighting the “language drama” that would permeate her writing. In fact, these are marks that stand out in the Clarician texts and seem to have eclipsed another fundamental facet for the understanding of her work: the concern with social issues. In this article, we propose a reading of The Hour of the Star that is concerned with analyzing the work focusing on social criticism and its aesthetic composition. We conclude, in the light of the reading of Jacques Rancière’s Politics of Aesthetics: The Distribution of the Sensible that ethical engagement is linked to the aesthetic, and the Clarice’s work is permeated by these encounters in very subtle ways.